Optimization of wear behaviour for AA2219-MoS2 metal matrix composites in dry and lubricated condition. (2020) - Rajesh kumar, L.; Saravanakumar, A.; Bhuvaneswari, V.; Gokul, G.; Dinesh kumar, D.; Jithin karunan, M.P.
Abstract: Composite materials are tailor made materials with two insoluble phases which in combination gives better properties than conventional monolithic materials. Metal matrix composites (MMCs) has gained much limelight during the recent days due to the possession of enormous advantages and variety of applications. Aluminium matrix composites are widely employed in contact applications like brake drum, cylinder linings etc. due to its light weight, excellent wear and corrosion resistance. Self-lubricating materials like molybdenum di sulphide (MoS2 ) and graphite (Gr) improve the wear resistance of the aluminium MMCs. Study of tribological behaviour of composites under lubrication can also be done by using recycled oils extracted from discarded wastes like plastics, tyres etc., This promotes the recyclability and decreases the effects of such discarded wastes over the environment. In the current work aluminium alloy AA2219 is reinforced with molybdenum di sulphide (MoS2 ) through stir casting. Wear properties of the composites were measured and optimized in dry and lubricated condition in a pin-on-disc apparatus. For lubrication tyre oil and tyre oil nano fluid suspended with alumina is used. Experiments were randomized and designed using Taguchi method and L27 orthogonal array (OA) was used for the conduct of experiments. Dry sliding wear behaviour of AA2219-MoS2 composites were compared with the tyre oil as a lubricant. Wear behaviour of AA2219-MoS2 composites were found to be much lower when lubricated with tyre oil. It was understood from the experiments that tyre oil could be used as a viable lubricant in contact applications.